2022
DOI: 10.1177/01455613221115043
|View full text |Cite
|
Sign up to set email alerts
|

Co-Treatment with Steroid and Dupilumab for Eosinophilic Chronic Rhinosinusitis after Eosinophilic Pneumonitis Caused by Dupilumab

Abstract: Eosinophilic chronic rhinosinusitis (ECRS) is a Type 2 inflammatory disease that manifests as chronic inflammation of the paranasal sinus. IL-4/IL-13 receptor monoclonal antibodies (dupilumab) to suppress Type 2 inflammation have become a good treatment option for patients who are refractory to surgery. Most patients respond normally, although significant side effects such as eosinophilic pneumonia may occur, requiring discontinuation of dupilumab. Here, we present a case in which dupilumab administration caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Only one patient in the literature ( 11 ), along with our patient, resumed dupilumab therapy. The patient in the literature used it in combination with 10 mg of prednisone for 10 months without recurrence of pneumonia.…”
Section: Literature Review Of Dupilumab-related Ep Casesmentioning
confidence: 84%
“…Only one patient in the literature ( 11 ), along with our patient, resumed dupilumab therapy. The patient in the literature used it in combination with 10 mg of prednisone for 10 months without recurrence of pneumonia.…”
Section: Literature Review Of Dupilumab-related Ep Casesmentioning
confidence: 84%
“…Sudo et al reported a patient with ECRS who developed dupilumab‐induced EP. 8 In that case, dupilumab was resumed in combination with PSL after the treatment of EP.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have found that dupilumab can cause EP, while others have described EP treated with dupilumab. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 The mechanisms underlying dupilumab‐induced EP remain unclear. However, previous reports of EP after dupilumab treatment suggest an association with hypereosinophilia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, reports have not been described regarding recurrence of adverse events after restarting dupilumab. Sudo et al recommend that a combination of a low-dose steroids and dupilumab, after countering the side-effect of eosinophilic pneumonia induced by dupilumab alone, be used in order to continue injecting dupilumab [ 11 ]. However, since there is no established method of dealing with the disease, verification of pathological characteristics and factors that trigger the onset of EP, as well as verification of changes in peripheral blood eosinophils, are desirable in the future.…”
Section: Mechanism Of Eosinophil Increase With Dupilumabmentioning
confidence: 99%